2001
DOI: 10.1046/j.1432-1327.2001.02232.x
|View full text |Cite
|
Sign up to set email alerts
|

The pro‐sequence facilitates folding of human nerve growth factor fromEscherichia coliinclusion bodies

Abstract: Nerve growth factor (b-NGF), a neurotrophin required for the development and survival of specific neuronal populations, is translated as a prepro-protein in vivo. While the presequence mediates translocation into the endoplasmic reticulum, the function of the pro-peptide is so far unknown. As the pro-sequences of several proteins are known to promote folding of the mature part, the renaturation behaviour of recombinant human b-NGF pro-protein was compared to that of the mature form. Expression of rh-pro-NGF in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
127
2
3

Year Published

2004
2004
2009
2009

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 125 publications
(147 citation statements)
references
References 38 publications
(34 reference statements)
15
127
2
3
Order By: Relevance
“…In case of NGF, the pro-form has recently been attributed pro-apoptotic functions (13,15). In addition, we have previously demonstrated that the pro-peptide significantly contributes to in vitro oxidative folding (10,11). The original objective of the presented work was to show a similar role for the pro-peptide of BMP-2.…”
Section: The Mature Part Of Bmp-2 Influences the Spectroscopic Propermentioning
confidence: 88%
See 2 more Smart Citations
“…In case of NGF, the pro-form has recently been attributed pro-apoptotic functions (13,15). In addition, we have previously demonstrated that the pro-peptide significantly contributes to in vitro oxidative folding (10,11). The original objective of the presented work was to show a similar role for the pro-peptide of BMP-2.…”
Section: The Mature Part Of Bmp-2 Influences the Spectroscopic Propermentioning
confidence: 88%
“…Because we had shown previously that the pro-form of NGF can also be cleaved in vitro by trypsin to obtain mature NGF (11), this protease was used to test maturation of proBMP-2 to BMP-2. Proteolysis with trypsin resulted in N-terminally truncated BMP-2 (Fig.…”
Section: The Pro-peptide Plays No Significant Role During In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…Inclusion bodies were isolated from cell pellets, solubilized, and protein was refolded as described (27,33). Refolded protein was purified by fast protein liquid chromatography and eluted in 50 mM sodium phosphate, pH 7, 1 mM EDTA, 2 M NaCl.…”
Section: Methodsmentioning
confidence: 99%
“…In Alzheimer disease brain, retrograde transport from the cortex and hippocampus to basal forebrain cholinergic neurons is reduced as these neurons degenerate, with concomitant proNGF accumulation in the cortex and hippocampus (21,23). This suggested that proNGF mediates biological activity besides its prodomain function of promoting protein folding and regulation of neurotrophin secretion (25)(26)(27)(28). To study the role of proNGF protein in vitro, point mutations were inserted at the cleavage site used by furin, a proprotein convertase known to cleave proNGF (29), to minimize the conversion of proNGF to mature NGF.…”
mentioning
confidence: 99%